Prototype Digester Berpengaduk dan Sensor Pendeteksi Gas methane Berbasis IoT - Muhammad Zhaky; Eko Supriadi (Jurnal Sains dan Teknologi, 2024)
Spentwash, a liquid waste byproduct of bioethanol production, is a potential raw material for biogas production due to its high organic content and abundant availability. PT Energi Agro Nusantara (ENERO) utilizes spentwash through anaerobic digestion processes to produce biogas, which is used as an alternative energy source.However, optimizing biogas production still faces various challenges, including the need for efficient monitoring and increased production volume. Internet of Things (IoT)-based technology offers a solution through real-time monitoring systems, enabling direct and accurate methane level measurements.This study aims to develop a prototype of a stirred digester equipped with an IoT-based methane gas detection sensor, using the MQ-2 sensor to detect methane gas.